Implementasi Peraturan Walikota Nomor 6 Tahun 2021 di Kota Padangsidimpuan - Ian Alfian (Jurnal AKTUAL, 2022)
This study aims to determine the consistency of the implementation of Mayor Regulation Number 6 of 2021 in Padangsidimpuan City concerning the Arrangement and Development of People's Markets, Shopping Centers and Supermarkets and Layouts in Padangsidimpuan City. This type of research is a descriptive qualitative research by interviewing the local government regarding the regulations that have been issued and the implementation of these regulations. The results of the study show that so far the government has consistently implemented this rule as well as possible. It is shown that the granting of permits for the establishment of modern retail which is not in accordance with regulations, the government still does not grant permits to modern retail entrepreneurs. For example Alfamidi who is on Jl Imam Bonjol Padangsidimpuan. Then the role of the government in this case the Department of Cooperatives, MSME and Trade also urges through the regulation to modern retail entrepreneurs to: accept employees from the surrounding community, provide stalls for MSME in front of modern retail and accept MSME products to be marketed in modern retail.